2009
DOI: 10.1128/jb.01103-08
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol Metabolism Is Important for Cytotoxicity of Mycoplasma pneumoniae

Abstract: Glycerol is one of the few carbon sources that can be utilized by Mycoplasma pneumoniae. Glycerol metabolism involves uptake by facilitated diffusion, phosphorylation, and the oxidation of glycerol 3-phosphate to dihydroxyacetone phosphate, a glycolytic intermediate. We have analyzed the expression of the genes involved in glycerol metabolism and observed constitutive expression irrespective of the presence of glycerol or preferred carbon sources. Similarly, the enzymatic activity of glycerol kinase is not mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
177
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(183 citation statements)
references
References 33 publications
6
177
0
Order By: Relevance
“…Previously, glycerol oxidation by mycoplasmas was shown to generate H 2 O 2 , a major product for cytotoxicity (37,38). Figure 4 shows that although both strains grew well with glucose, they exhibited slow growth with glycerol, as was previously reported for M. pneumoniae (37), with the ⌬MG_427 mutant exhibiting significantly slower growth. These data suggest a protective role of MG_427 against H 2 O 2 .…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…Previously, glycerol oxidation by mycoplasmas was shown to generate H 2 O 2 , a major product for cytotoxicity (37,38). Figure 4 shows that although both strains grew well with glucose, they exhibited slow growth with glycerol, as was previously reported for M. pneumoniae (37), with the ⌬MG_427 mutant exhibiting significantly slower growth. These data suggest a protective role of MG_427 against H 2 O 2 .…”
Section: Resultssupporting
confidence: 56%
“…Further, we demonstrated that the ⌬MG_427 strain of M. genitalium exhibited hypersensitivity to t-BHP and increased sensitivity to H 2 O 2 and this sensitivity could be reversed in the mutant strain complemented with an intact MG_427 gene, similar to osmC mutants of E. coli (24) and M. smegmatis (25). We also observed a slower growth of the ⌬MG_427 mutant than the wild type in SP-4 medium containing glycerol as the carbon source, a growth condition known to generate H 2 O 2 by mycoplasmas (37,38). Altogether, these data suggest that MG_427 encodes a hydroperoxide reductase which likely plays an important role in protecting M. genitalium against oxidative stress.…”
Section: Discussionmentioning
confidence: 50%
“…The formation of a unique tip-like structure comprising a complex of adhesins and adhesion-related proteins was shown to be the basis for effective adherence of bacteria to the respiratory mucosa (Krause & Balish, 2004). The further colonization process is accompanied by the release of hydrogen peroxide (Hames et al, 2009;Schmidl et al, 2011) and of the pertussis toxin-like CARDS toxin (Kannan & Baseman, 2006), resulting in vacuolization and destruction of epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…mycoides [28,29]. In line with that, it was recently demonstrated that pathogenic strains of M. hyopneumoniae were able to produce hydrogen peroxide from glycerol metabolism, but that the non-pathogenic strain J and M. flocculare were not [11].…”
Section: Discussionmentioning
confidence: 85%